Consumer behaviour and accessibility: A classification of food consumers in Mainfranken, Germany Konsumverhalten bei Lebensmitteleinkäufen und verkehrliche Erreichbarkeit: eine Typisierung von Verbraucher/-innen am Beispiel der Region Mainfranken - Erhard, Lena; Rauh, Jürgen; Rauch, Sebastian (Raumforschung und Raumordnung, 2025)
With the increasing decline of basic supply networks, both the organization of grocery shopping and perceptions of accessibility have shifted. In light of the many factors that shape shopping behaviours, preferences, and evaluations, this paper aims to classify consumer types. Based on a household survey, three consumer clusters were identified using cluster analysis: (1) environmentally conscious, pedestrian-oriented shoppers; (2) pragmatic, trip-chaining, quality-conscious shoppers; and (3) car-oriented shoppers focused on discounters and supermar-kets. These clusters differ in their mobility and shopping pref-erences, their criteria for selecting shopping locations, and the extent to which they use nearby stores. While the environmentally conscious cluster frequently prefers smaller, regional out-lets and completes many trips on foot or by bicycle, the other two clusters rely predominantly on automobiles. Notably, the pragmatic cluster combines grocery trips with other activities, such as commuting. The findings indicate that the decline of local shops disproportionately impacts environmentally conscious and non-motorized consumers. This approach enables consumer segmentation not only by shopping behaviour but also by mobility patterns and subjective assessments.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Accessibility; Food supply; Mainfranken; Mobility; Shopping behaviour